Methods, Mechanisms and Typical Bio‐Indicators of Engineered Nanoparticle Ecotoxicology: An Overview. Issue 4 (30th August 2013) - Zhuang, Wen; Gao, Xuelu
<x xml:space="preserve">Abstract</x> As nanotechnology industries increase production, increased release of engineered nanoparticles (NPs) to aquatic environments suggests a rising need for monitoring and evaluation of their potential toxicity. Based on previous and latest research results in the related field, this paper reviews methods, mechanisms, and typical bio‐indicators of nanomaterials ecotoxicological research. It outlines detecting methods of NPs in ecotoxicologial studies, and discusses suspension methods of nanoparticles in this field. Proteomics and genomics technologies are predicted to be indispensable means in ecotoxicological studies of NPs. It also points out that biology of particle‐induced oxidative stress is an important mechanistic paradigm, and so are solvent effects and the effects of NPs on other substances. Typical bio‐indicators in aquatic systems are claimed to be determined to avoid unnecessary animal testing whenever possible and to reduce unnecessary testing costs. In ecotoxicological research of NPs, fish species are generally considered as preferred species; for nanoparticle ecotoxicity, suspension‐feeding invertebrates may be a unique target group, therefore invertebrate testing is also very important; because of sensitivity to pollutants, phytoplankton testing should be strengthened. This paper also summarizes some conflicting results in current experiments, and gives some possible explanations. Finally, future research directions are proposed.